The Role of Physiotherapy in Pediatric Palliative Care: A Systematic Review - Silvia Ortiz-Campoy; Cristina Lirio-Romero; Helena Romay-Barrero; David Martín-Caro Álvarez; Purificación López-Muñoz; Rocío Palomo-Carrión (MDPI AG, 2021)
Pediatric palliative care (PPC) is a set of actions aimed at children who suffer from a severe or life-threatening disease to alleviate the symptoms of the disease and improve the quality of life of both the child and his/her family. One of the tools used to control symptoms is physiotherapy; however, its application in the child population has not been thoroughly studied. The main objective of this study was to gather, analyze, and critically evaluate the available scientific evidence on physiotherapy in children who require palliative care through a systematic review of the studies published in the last 10 years in the following databases: PubMed, Cochrane Library, PEDro, CINAHL, and Scopus. Of a total of 622 studies, the inclusion criteria were only met by seven articles, which were focused on the relationship between physiotherapy and PPC. This study analyzed: (1) the main pathologies treated, with a predominance of cerebral palsy and cancer; (2) the interventions applied, such as respiratory physiotherapy, neurological physiotherapy, therapeutic massage, and virtual reality; (3) the effects achieved in the child and his/her family, highlighting the control of symptoms and the improvement of the quality of life; and (4) the knowledge of the physiotherapists on PPC, observing that most of the professionals had not received training in this scope. The findings of this review indicate a lack of an adequate evidence foundation for physiotherapy in PPC.